An analytical study of sound transmission through corrugated core FGM sandwich plates filled with porous material. (15th October 2018) - Fu, Tao; Chen, Zhaobo; Yu, Hongying; Wang, Zhonglong; Liu, Xiaoxiang
Abstract: The main objective of this research work is focused on sound transmission loss analysis of corrugated core functionally graded material (FGM) sandwich plates filled with porous material, wherein two types of FGM sandwich structures are considered, which include one with FGM face sheets and homogeneous ceramic or metal core, and the other with FGM core and homogeneous face sheets. To model the process of sound propagation between fluid and solid, the equivalent fluid model with effective density and bulk modulus is used to describe the sound wave propagation through porous sound absorptive material. The corrugated cores are approximated as a series of uniformly distributed translational and rotational springs to link the sandwich structure. Fluid-structure coupling is considered by imposing velocity continuity condition at fluid-structure interfaces. By using the space harmonic approach and virtual work principle, the sound transmission loss is described analytically. The validity of the proposed theoretical model is verified by comparisons with previously published numerical results. Based on the developed theoretical mode, the influences of the FGM properties, gradient index, sandwich type, skin-core-skin ratios and porous material type on sound transmission loss are subsequently presented.